Cognitive Impact of Deep Brain Stimulation in Parkinson’s Disease Patients: A Systematic Review - Rački, Valentino; Hero, Mario; Rožmarić, Gloria; Papić, Eliša; Raguž, Marina; Chudy, Darko; Vuletić, Vladimira (Frontiers in Human Neuroscience, 2022)
Introduction: Parkinson’s disease (PD) patients have a significantly higher risk of developing dementia in later disease stages, leading to severe impairments in quality of life and self-functioning. Questions remain on how deep brain stimulation (DBS) affects cognition, and whether we can individualize therapy and reduce the risk for adverse cognitive effects. Our aim in this systematic review is to assess the current knowledge in the field and determine if the findings could influence clinical practice. Methods: We have conducted a systematic review according to PRISMA guidelines through MEDLINE and Embase databases, with studies being selected for inclusion via a set inclusion and exclusion criteria. Results 67 studies were included in this systematic review according to the selected criteria. This includes 6 meta-analyses, 18 randomized controlled trials, 17 controlled clinical trials, and 26 observational studies with no control arms. The total number of PD patients encompassed in the studies cited in this review is 3677, not including the meta-analyses. Conclusion: Cognitive function in PD patients can deteriorate, in most cases mildly, but still impactful to the quality of life. The strongest evidence is present for deterioration in verbal fluency, while inconclusive evidence is still present for executive function, memory, attention and processing speed. Global cognition does not appear to be significantly impacted by DBS, especially if cognitive screening is performed prior to the procedure, as lower baseline cognitive function is connected to poor outcomes. Further randomized controlled studies are required to increase the level of evidence, especially in the case of globus pallidus internus DBS (GPi-DBS), pedunculopontine nucleus DBS (PPN-DBS) and the ventral intermediate nucleus of thalamus DBS (VIM-DBS), and more long-term studies are required for all respective targets.